Preserving I Gede Modara’s “Rotating the Mountain of Mandara Giri” Painting - Mudana, I Wayan; Wirakesuma, I Nengah; Kondra, I Wayan; Sujana, I Wayan; Mustika, I Ketut (Indonesian Journal of Multidisciplinary Science, 2023)
I Gede Modara (1770), nicknamed I Gede Mersadi, was a pioneer of the Kamasan wayang painting, which is now called classical balinese painting. Kamasan wayang paintings are very bound by standards and provisions that are binding and standard, used for offerings and enlightenment to the people. One of the works left by Modara enlightenment painting, entitled "Pemuteran Gunung Mandara Giri" is made in the form of parba on wood, using balinese colors, now in very poor condition, not taken care of properly, and has not received attention from the government so that it gives the impression of being very neglectful of the heritage history. In fact, this work is a work that has a high reputation as an art historical heritage which is very important when future generations want to trace the civilization and development of balinese classical painting. Departing from this phenomenon, it is interesting to be used as research "Preservation of I Gede Modara's Painting with the title Screening of Mount Mandara Giri". The analytical approach used the concept of theory and method of preservation. Preservation relates to preservation, development and empowerment to create new or renewable products. In the discussion, discussing: 1) conservation measures, 2) development of creative industries, 3) community empowerment and expanding employment opportunities.